Bedazzled Bollywood Costumes: Understanding Cloth, Context, and Creation. (3rd July 2019) - Chatterjee, Deepsikha; Vasek, Cheri
Abstract : This paper aims to illustrate Indian film costume creation. To better understand these colorful, highly adorned, and powerful expressions of global material culture, the authors—US-based costume designers—investigate the background from which these costumes emerge, exploring who envisions them, who creates them, who wears them, and what tangible resources make them possible. The authors discuss how film costume production is shaped by skilled artisans who use extraordinary materials and techniques available in India and employ unique production processes to create costumes for compelling narratives. Findings from field research and interviews, along with a look at the influence of contemporary fashion trends on costume production, are discussed and analyzed.